PENGEMBANGAN INSTRUMEN TES DIAGNOSTIK TWO-TIER UNTUK MENGIDENTIFIKASI MISKONSEPSI PADA MATERI POKOK CAHAYA SISWA SMP - Marissa Dwi Lestari; Zuhdi Ma’ruf; Fakhruddin Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Misconceptions cause new knowledge that students have cannot be connected with their cognitive knowledge so that the understanding of the student's concept becomes weak. This indicates that misconceptions need to be identified as early as possible. One way to identify misconceptions is to use diagnostic test instruments. The study aims to develop two-tier diagnostic tests on light subject matter. The development model used is the 4-D model namely define, design, develop, and disseminate. Data analysis of the test results of this test instrument in grade 1X junior high school students showed validity based on the validity of the question item with the number of 12 questions, reliability of 0.9781 with a very high category, the problem item with difficulty level amounted to 11 questions and medium difficulty level of 9 questions, with excellent differentiating power amounted to 2 points , good category differentiating power 4 points of question, differentiating power with a category of enough amounts to 8 points of question, differentiating power with poor criteria amounting to 4 points of questions and 2 points of problems with negative discrimination values. The results showed that the two-tier diagnostic test instruments developed were feasible to identify misconceptions of light subject matter.Key Words: Two-Tier Diagnostic Test, Misconceptions, Light